Optimalisasi Lahan Pekarangan Sekolah sebagai Kebun Gizi dalam Upaya Peningkatan Konsumsi Sayur Bagi Siswa SD Negeri 3 Metro Pusat - Ambar Sari, Novia; Mandala, Wintari; Novita; Ivan’s, Eny; Indaryati, Sri (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2024)
Implementation of the Independent Curriculum (IKM) at the elementary school level can be realized by establishing collaboration between universities and schools. This collaboration is a form of knowledge transfer from higher education institutions to students. Hands-on practical activities such as farming have many benefits for students. Utilizing the school yard is the basic reason as well as being a learning medium for students. The implementation of PKM was carried out using lecture and FGD methods. The activity began with socialization on the use of school yard land and added the practice of hydroponic and verticulture farming using used bottles. The results of the activity are optimizing the yard area around the school by cultivating vegetable plants using a verticulture system. Apart from that, students gain direct knowledge and practice in making planting containers from used bottles and maintaining them until the vegetable plants are ready to be processed and consumed. One of the MBKM Programs is the Pancasila Student Profile which is the character traits and competencies that students are expected to achieve, which is based on the noble values of Pancasila. Students are expected to be able to modify and produce something original, meaningful, useful and impactful.